2016
DOI: 10.1590/1809-4392201504341
|View full text |Cite
|
Sign up to set email alerts
|

Floristic and structure of an Amazonian primary forest and a chronosequence of secondary succession

Abstract: The analysis of changes in species composition and vegetation structure in chronosequences improves knowledge on the regeneration patterns following land abandonment in the Amazon. Here, the objective was to perform floristic-structural analysis in mature forests (with/without timber exploitation) and secondary successions (initial, intermediate and advanced vegetation regrowth) in the Tapajós region. The regrowth age and plot locations were determined using Landsat-5/Thematic Mapper images . For floristic ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
2
11
0
1
Order By: Relevance
“…Previous studies have found a positive relationship between biomass recovery (which is related to basal area) and biodiversity (e.g. Marín-Spiotta et al 2007;Letcher and Chazdon 2009;Silva et al 2016, Lennox et al 2018. Overall, basal area (or related measures, such as biomass) is a good indicator of structural changes in the regenerating forests (Lennox et al 2018), such as increasing canopy cover and soil organic matter, which favour the establishment of more species.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Previous studies have found a positive relationship between biomass recovery (which is related to basal area) and biodiversity (e.g. Marín-Spiotta et al 2007;Letcher and Chazdon 2009;Silva et al 2016, Lennox et al 2018. Overall, basal area (or related measures, such as biomass) is a good indicator of structural changes in the regenerating forests (Lennox et al 2018), such as increasing canopy cover and soil organic matter, which favour the establishment of more species.…”
Section: Discussionmentioning
confidence: 87%
“…Recovery rate of the structure and diversity of plant species in secondary forests are determined by a complex interaction between local, historical and landscape factors, as well as the regional species pool and their life history traits (Chazdon et al 2007). Forest recovery is related to several intrinsic factors, such as time since abandonment (Prata et al 2010;Silva et al 2016), land-use history (Jakovac et al 2015;Villa et al 2018), soil characteristics and landscape structure (Jakovac et al 2015;Pinho et al 2018;Do vale et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Field plot data were composed by two databases: 16 plots measured in this study and 26 plots measured by Silva [64] (Table 1). The sample plots were placed close to the FLONA of Tapajós on either side of the BR-163 highway, 100 km to the south of the city of Santarém (Figure 1).…”
Section: Field and Satellite Imagery Datamentioning
confidence: 99%
“…Trees with a DBH ≥ 10 cm were measured in a 20 m × 100 m plot size, and trees with a DBH ≥ 20 cm were measured in a 60 m × 100 m plot size. Silva [64] carried out a field campaign between 2012 and 2013 at the same site ( Table 1). The method consisted of the collection of 23 plots (20 m × 50 m) for the SF with initial secondary succession (ISS) and intermediate secondary succession (IntSS), and three plots for the advanced SF (25 m × 100 m).…”
Section: Field and Satellite Imagery Datamentioning
confidence: 99%
See 1 more Smart Citation